Daur Qāmūs Inthiq! fī Taḥsīn Mahārat al Kalām min Khilāl Maqārabat al Ta‘allum al‘Amīq fī Ma‘had Al Kautsar Dendang - Sitti Arafah Utari (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2025)
This study aims to describe and analyze the role of Kamus Inthiq! in enhancing students’ speaking skills (maharah kalām) through a deep learning approach at Pondok Pesantren Al-Kautsar Dendang. Kamus Inthiq! is an innovative, thematic, and digital-based learning medium specifically designed to help students understand, memorize, and use Arabic vocabulary in various communicative and real-life contexts. This research employed a descriptive-qualitative method with a field study approach, involving observations, interviews, and documentation to gain a comprehensive understanding of its application. The findings indicate that the active and consistent use of Kamus Inthiq! in Arabic learning activities significantly contributes to students’ vocabulary enrichment, contextual understanding, and the development of speaking confidence and fluency. The deep learning approach applied in this process emphasizes repetition, reflection, and experiential learning, enabling students to internalize language patterns more effectively. Furthermore, Kamus Inthiq! does not merely function as a static digital dictionary, but as an interactive learning medium that promotes student engagement, collaboration, and communication-oriented learning experiences. Its integration into the curriculum also supports a more dynamic and student-centered Arabic language learning environment.